Epidemiology of Meningococcal Disease Outbreaks in the United States, 2009–2013. (30th June 2018) - Mbaeyi, Sarah A; Blain, Amy; Whaley, Melissa J; Wang, Xin; Cohn, Amanda C; MacNeil, Jessica R
Abstract : Outbreaks account for 5% of US meningococcal disease cases. Serogroups B and C are the primary causes of organization- and community-based outbreaks, respectively. University students and men who have sex with men were disproportionately affected during this period. Abstract: Background: Although the incidence of meningococcal disease is low in the United States, outbreaks remain a serious public health concern. In this evaluation, we identify and describe outbreaks of meningococcal disease. Methods: A retrospective review of all meningococcal disease cases reported from 1 January 2009 to 31 December 2013 was performed by state health departments and the Centers for Disease Control and Prevention to identify meningococcal disease outbreaks. An outbreak was defined as ≥2 primary cases of the same serogroup within <3 months in an organization, or a ≥2-fold increase in disease rates in a community. Results: From 2009 to 2013, a total of 3686 cases of meningococcal disease were reported in the United States. Among these, 180 primary cases (4.9%) occurred as part of 36 outbreaks (17 organization-based and 19 community-based). Serogroup B accounted for 8 (47.1%) of the organization-based outbreaks, including 6 of 8 university outbreaks. Serogroup C accounted for 10 (52.6%) of the community-based outbreaks, including both of 2 outbreaks identified among men who have sex with men. Organization- and community-based outbreaks differed in predominant serogroup, age distribution of cases, and clinical syndrome. Among 33 outbreaks with known information, a vaccination and/or expanded chemoprophylaxis campaign was conducted in 16 (48.5%). Conclusions: Outbreak-associated cases account for approximately 5% of all meningococcal disease cases in the United States. Serogroup B is the primary cause of organization-based outbreaks, with the majority of university outbreaks due to serogroup B, and serogroup C is the primary cause of community-based outbreaks.